Temperature gradient‐aware thermal simulator for three‐dimensional integrated circuits. Issue 5 (1st August 2017) - Lu, Liang‐Ying; Chiou, Lih‐Yih
Abstract : Nowadays, thermal simulators of integrated circuits (ICs) at architectural level tend to neglect thermal effects in temperature‐dependent factors (such as leakage power and thermal conductivity) and a heat dissipation mechanism for thermal radiation at the early stages of IC design. Hence, the analysis results of thermal simulators may be not sufficient to reflect the physical–thermal interactive effects of ICs. This study presents a temperature gradient‐aware thermal simulator for three‐dimensional ICs (called 3D‐TarGA) at the architectural level. The temperature gradient‐aware thermal analysis of 3D‐TarGA considers the thermal effects in leakage power, thermal conductivity, thermal radiation, and thermal convection to reflect the physical–thermal interactive effects of ICs at the early stages of IC design. Experimental results show that the maximum absolute error for the temperature of IC with ignoring the thermal effects using 3D‐TarGA is 1.62°C, in contrast to the published thermal simulator, HotSpot. Moreover, the maximum absolute difference for the temperature of IC by considering the thermal effects is 2.7°C, as compared with that when ignoring the thermal effects for 3D‐TarGA.